Overcoming difficulties in implementing a universal newborn hearing screening program - Korres, Stavros; Balatsouras, Dimitrios G; Vlachou, Stamatia; Kastanioudakis, Ioannis G; Ziavra, Nausica V; Ferekidis, Eleftherios (The Turkish Journal of Pediatrics, 2005)
The aim of this paper was to present our experience with a universal newborn hearing screening program, including the specific problems and difficulties faced since its beginning, along with the measures used to overcome them and to improve its efficiency. We analyzed data from 22,195 newborns screened by transiently evoked otoacoustic emissions (TEOAE) performed during the first days after birth. 84.8% of the newborns passed on the first test and another 12.15% passed on rescreening before hospital discharge. This produced a "not pass" rate (false-positive and true positive) of 3.05%. The rate of newborns who did not undergo screening and the rate of "lost to follow-up" newborns were reduced in time, due to various applied modifications to the protocol. It may be thus concluded that our protocol proved to be successful in attaining low refer rates for follow-up screening. A major problem that remains unresolved is the absence of effective follow-up.